PELAKSANAAN PEMBELAJARAN MUSIK BERBASIS KOMUNITAS TEMAN SEBAYA MELALUI EKSTRAKURIKULER MARCHING BAND DI SMP NEGERI 29 PADANG - Yolandri, Yuri; Ardipal (Universitas Negeri Padang, 2026)
Marching band activities provide a platform for students to learn music and improve teamwork, discipline, and communication skills among members. This study aims to examine the implementation of peer-based music learning through extracurricular marching band activities at SMP Negeri 29 Padang. The study used a qualitative approach with a descriptive approach. Data was obtained through observation, interviews, and documentation with instructors, coaches, and marching band members. The results indicate that the learning process is carried out through routine practice, providing examples of material, group practice, and joint evaluation. Peers play a crucial role in helping students understand the material, fostering enthusiasm for learning, and strengthening group cohesion. Supporting factors in this activity include school support, student enthusiasm, and the presence of coaches. Barriers include limited equipment, limited practice time, and differences in student abilities.